ACL Reconstruction: Problems, History and Future. Part II - Zazirnyi, I.M.; Kostrub, O.O. (TERRA ORTHOPAEDICA, 2020)
Summary. Anterior cruciate ligament (ACL) injury is one of the most commonly seen injuries in sport and has a devastating influence on patients’ activity levels and quality of life. For patients, whose history and results of physical examination suggest an ACL injury, MRI is indicated to confirm the diagnosis and to determine whether there are concomitant injuries. There are limited data of the need for immediate ACL reconstruction. Surgeons need to discuss with the patient the option of a structured accelerated course of rehabilitation as an alternative to immediate reconstruction. If an initial strategy of rehabilitation was chosen, serial evaluation of knee function and functional recovery in the first 3 months after the injury would recommend. If there is residual instability (greater than grade 2) at the time of subsequent assessment, the surgery is necessary to avoid further damage to the articular cartilage and meniscus. When reconstruction is advised as the correct management of an ACL injury, there are various options. The type of a graft, single-bundle or double-bundle reconstruction, graft placement, and whether to use the transtibial, far anteromedial portal, or tibial tunnel–independent technique are choices that must be made. Each option has its own advantages and disadvantages, with single- or double-bundle strategy, proper placement of grafts, and the use of autografts affect the clinical outcome and quality of life of patients. The selection of the best autograft tissue type remains controversial, with the patellar tendon (PT), the hamstring (HS) tendon, and the quadriceps tendon each having their proponents.